Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a^3+b^3+12ab\)
\(=\left(a+b\right)^3-3ab\left(a+b\right)+12ab\)
\(=4^3-3ab.4+12ab\)
\(=4^3-12ab+12ab\)
\(=4^3=64\)
a3 + b3 + 12ab
= (a + b)(a2 - ab + b2) + 12ab
= 4(a2 - ab + b2) + 12ab
= 4(a2 - ab + b2 + 3ab)
= 4(a2 + 2ab + b2)
= 4(a + b)2
= 4.42 = 64
Vậy a3 + b3 + 12ab = 64 (với a + b = 4)
a) M = a3 + b3 + 12ab
.........= (a + b)(a2 - ab + b2) + 12ab
.........= 4a2 - 4ab + 4b2 + 12ab
.........= 4a2 + 8ab + 4b2
.........= a2 + 2ab + b2 = (a + b)2 = 42 = 16
a) N = x3 - y3 - 9xy
........= (x - y)(x2 + xy + y2) - 9xy
........= 3x2 + 3xy + 3y2 - 9xy
........= 3x2 - 6xy + 3y2
........= x2 - 2xy + y2 = (x - y)2 = 32 = 9
a/ \(x^3+3xy+y^3=x^3+3xy.1+y^3=x^3+y^3+3xy\left(x+y\right)=\left(x+y\right)^3=1\)
b/ \(x^3+y^3=\left(x+y\right)^3-3xy\left(x+y\right)=a^3-3a\left(xy\right)=a^3-\frac{3a\left(a^2-b\right)}{2}=\frac{3ab}{2}-\frac{a^3}{2}\)
c/ Không rõ đề
\(B=a^3-12ab-b^3\)
\(=\left(a-b\right)^3-12ab+3ab\left(a-b\right)\)
\(=\left(a-b\right)^3-3ab\left[4-\left(a-b\right)\right]\)
\(=64\)( vì a-b=4)
Vậy B có giá trị =64 khi a-b=4